2020
DOI: 10.3390/ma13122825
|View full text |Cite
|
Sign up to set email alerts
|

Hot-Deformation Behavior and Microstructure Evolution of the Dual-Scale SiCp/A356 Composites Based on Optimal Hot-Processing Parameters

Abstract: Hot deformation at elevated temperature is essential to densify particle-reinforced aluminum matrix composites (AMCs) and improve their performance. However, hot deformation behavior of the AMCs is sensitive to the variation of hot-processing parameters. In this paper, optimal processing parameters of dual-scale SiCp/A356 composites were determined to explore the control strategy of the microstructure. Hot-compression tests were conducted at temperatures ranging from 460 to 520 °C under strain rates from 0.01 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…To enhance the mechanical properties of composites, hot-working processing techniques, such as hot rolling [18], hot extrusion [19], and die forging, [20] can be employed. In recent years, extensive research has been conducted on the hot deformation behavior of composites, which has provided fundamental theoretical guidance for their hot working [21][22][23][24]. Generally, particles can stimulate nucleation on recrystallization, making the composites form a uniform and fine recrystallization microstructure during deformation [3,25].…”
Section: Introductionmentioning
confidence: 99%
“…To enhance the mechanical properties of composites, hot-working processing techniques, such as hot rolling [18], hot extrusion [19], and die forging, [20] can be employed. In recent years, extensive research has been conducted on the hot deformation behavior of composites, which has provided fundamental theoretical guidance for their hot working [21][22][23][24]. Generally, particles can stimulate nucleation on recrystallization, making the composites form a uniform and fine recrystallization microstructure during deformation [3,25].…”
Section: Introductionmentioning
confidence: 99%
“…However, the composites reinforced by nano particles are difficult to be prepare since nano particles are easy to agglomerate, limiting their application scopes [8,9]. In this case, the addition of micron and nano particles simultaneously into AMCs helps to solve the problem of insufficient strength and toughness, which is of great significance to promote the development of lightweight and wear-resistant AMCs [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Many research works revealed that the effects of particulates on deformation behavior of PRAMCs were complex [ 5 ]. Firstly, particles can hinder the motion of dislocations and grain boundary sliding (GBS) during deformation, leading to the accumulation of high-density dislocations around particles.…”
Section: Introductionmentioning
confidence: 99%